2021
DOI: 10.1002/pat.5449
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole derivatives for detection of toxic gases: A theoretical study

Abstract: Polypyrrole (PPy) based compounds have been considered interesting materials for several technological applications, mainly due to their unique optoelectronic properties and high versatility of synthesis. In particular, the sensitivity of their electrical properties to external stimuli defines these polymers as promising candidates for chemical sensor applications. However, the demanding processes involved in the synthesis of 3‐4 substituted PPy derivatives hinders the development of optimized systems. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Due to the strong influence of the effective conjugation length on the optoelectronic properties of these systems [ 28 , 61 ], representative oligomeric systems were considered in this study. In particular, studies conducted by our group and collaborators have shown that structures with 10–15 repeating units can reproduce the essential electronic and optical properties of these polymers [ 47 , 58 , 62 , 63 , 64 , 65 , 66 , 67 ]; for this reason, oligomers with 15 units were used.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the strong influence of the effective conjugation length on the optoelectronic properties of these systems [ 28 , 61 ], representative oligomeric systems were considered in this study. In particular, studies conducted by our group and collaborators have shown that structures with 10–15 repeating units can reproduce the essential electronic and optical properties of these polymers [ 47 , 58 , 62 , 63 , 64 , 65 , 66 , 67 ]; for this reason, oligomers with 15 units were used.…”
Section: Methodsmentioning
confidence: 99%
“…Coleone et al presented a theoretical study on polypyrrole derivatives for toxic gas detection where they analyzed derivatives such as PPY-F, PPY-NH 2 , PPY-OCH 3 , and PPY-OH. [175] After an extensive theoretical analysis they found that the PPY derivatives have strong interactions with most toxic gases, however they do have less extensive interactions with analytes such as AsH 3 , H 2 S, and PH 3 . This finding explains why there is less published work on PPY based H 2 S sensors.…”
Section: Hydrogen Sulfide Gas Sensorsmentioning
confidence: 99%